Metagenomic insights into microbial colonization & persistence in subsurface fractured shales - Amundson, Kaela K., author; Wilkins, Michael J., advisor; Wrighton, Kelly C., committee member; Borch, Thomas, committee member; Ross, Matthew, committee member (Colorado State University. Libraries, 2023)
Microorganisms are pervasive yet important components of hydraulically fractured shale systems. Subsurface shales harbor oil & gas and require unconventional techniques, such as hydraulic fracturing, to access these trapped hydrocarbons. Shale microbiomes are of crucial importance as they can directly impact the recovery of oil & gas and associated infrastructure. The overarching theme of this dissertation was to characterize the metabolisms and key traits that underpin the colonization and persistence of fractured shale microbiomes using a multi-omic approach to better understand the microbial impact on this important ecosystem. In Chapter 1, I first discuss the importance of subsurface shales as an important energy reserve, summarize what is known about microorganisms in these ecosystems, and highlight the strength of using a metagenomic approach to studying shale microbiomes. Subsurface shales are heterogeneous – varying in their mineral content, temperature, and other physiochemical conditions. The microbial communities that persist can have substantial impact on the fractured shale ecosystem and contribute to common challenges in hydrocarbon recovery such as corrosion, souring, and bioclogging. The literature review presented here highlights the need to study the functional potential of shale microbiomes as most studies have mostly focused solely on taxonomic composition of persisting microbial communities, and a vast majority of these studies have focused on samples from wells in the Appalachian Basin. However, functional potential of shale microbiomes across a variety of physiochemical conditions must be considered in order to gain an understanding of the role of microorganisms and what possible influences they may have on hydraulically fractured shales systems. Here, I highlight the need (1) to study the whole community at a functional scale and (2) apply a metagenomic approach to a variety of less characterized shale basins to gain a holistic understanding of shale microbiomes and the effects they may have on the broader ecosystem. In Chapter 2, I apply this metagenomic approach to study the persisting shale microbiomes of three fractured shale wells in the Anadarko Basin – a western shale basin characterized by elevated temperature and salinity. No studies using metagenomics had been applied to shale basins in the western United States prior to this research. We sampled five wells in the Anadarko basin over a timeseries >500 days and preformed NMR metabolomics and metagenomic sequencing to uncover the dominant metabolisms, community composition, and other functional traits of the Anadarko shale microbiome. This system was dominated by a fermentative microbial community and a less-abundant sub-community of inferred sulfate reducing microorganisms. Using paired NMR metabolomics and metagenomics, I demonstrated how many fermentative microorganisms have the potential to degrade common complex polymers, such as guar gum, and have potential to produce organic acids that may serve as electron donors for sulfate and thiosulfate reducing microorganisms. Thus, in this study I provided a framework for how carbon may move through the closed fractured shale ecosystem to sustain the microbial community. Finally, I investigated viral presence and diversity across all thirty-six metagenomes and found that inputs were large sources of viral diversity, but that only an extremely small proportion of viruses recovered from produced fluids were genetically similar to viruses previously reported from fractured shales. I observed that a majority of the dominant and persisting genomes encoded a CRISPR-Cas viral defense system, likely in response to the viral community. This highlights viral defense as another key trait for persisting microorganisms, as viruses are the only predators to bacteria and archaea in fractured shale ecosystems. Overall, this study expanded our knowledge of sulfate and thiosulfate reducing microorganisms in fractured shales, demonstrated the potential for common chemical inputs such as guar gum to be utilized by shale microbiomes, and highlighted how other key traits, such as CRISPR-Cas viral defense systems, may be a crucial trait for persisting shale microbiomes. Building on results from viral analyses in Chapter 2, in Chapter 3 I next sought to investigate the temporal dynamics between hosts and viruses to better understand the role of microbial defense against viruses in fractured shale ecosystems. To do this, I sampled six shale wells in the Denver-Julesburg Basin for >800 days, performed metagenomic sequencing, and identified host (bacterial & archaeal) and viral genomes from this data. I observed evidence of ongoing host defense to viral predation at both the community and genome-level through quantifying spacers from CRISPR arrays in metagenomic reads and MAGs. Through these analyses leveraging timeseries sampling and age differences between the shale wells, I provided evidence that suggested migration toward CRISPR arrays that may be more efficient at protecting the microbial host against a wider suite of viruses. Finally, I observed a temporal increase in host-viral co-existence in the closed, fractured shale ecosystem – suggesting the CRISPR defense does not entirely protect against viral predation. Chapter 4 ultimately leverages the approaches, insights, and data gained from Chapters 2 and 3 to study shale microbiomes at a cross-basin, geographic scale. Here, I collected samples from many collaborators who have previously worked in shale systems, performed metagenomic sequencing, and processed all samples in a standardized pipeline to build a comprehensive genomic shale database. In total, this database contains 978 unique MAGs and >7 million unique genes recovered from 209 metagenomic samples obtained from 36 fractured shale wells spanning eleven shale basins from North America, China, and the United Kingdom. In this chapter I analyze the functional potential of shale microbiomes at a genome-resolved level to better understand the geographic distribution of microbial metabolisms and other key traits that likely contribute to colonization and persistence of microorganisms. Here I also leveraged bioinformatic tools to build a custom annotation summary toolkit to process and analyze the large amount of sequencing data for traits of interest. The complete absence of a taxonomic core microbiome across shale basins illustrated in this chapter underscores the necessity of a genome-resolved and functional approach to studying shale microbiomes. Results from analyzing shale microbiomes at this scale could ultimately help to inform microbial management of fractured shale systems. The final chapter of this dissertation (Chapter 5) summarizes the key findings of my research into fractured shale microbiomes, and the mechanisms that may promote microbial colonization, persistence, and survival in these relatively harsh and economically relevant ecosystems. In this chapter I conclude this work by discussing future directions and lingering knowledge gaps for studying fractured shale microbiomes, as well as implications of these findings for other subsurface engineered ecosystems. Ultimately, this body of work contributes a substantial amount of new and informative insights into the functional potentials of persisting shale microbiomes across broad geographic scales.
Zip file contains appendices B and C.
Keywords: fractured shales; microbiome; biogeochemistry; subsurface; metagenomics